Online Learning Effectiveness and Instructor Resistance In Adult Learner Centered Extension Programs - Ernie Post (Adult Education Research Conference, 2009)
This paper reports the preliminary results of an ongoing mixed methods study to determine if the integration of online learning modules can help entrepreneurs accomplish business planning and elicit business start-up behavior. Insight is shared about why some adult learners and instructors are reluctant to migrate to online learning.
Keywords: online learning; blended learning; instructor resistance to online learning